(untitled) (Research, Society and Development, 2022)
Leishmaniasis are notifiable diseases, characterized by severe clinical manifestations, being caused by obligate intracellular protozoa, belonging to the genus Leishmania, where the species L. (L.) infantum and L. (V.) braziliensis are responsible for most cases. of leishmaniasis in Brazil. Many studies indicate the need for investigations into the exact role of animal species in the epidemiology of leishmaniasis, particularly of skunks and rodents, where the presence of these animals increases the chances of humans and other animals becoming infected. Considering the scarcity of information on the epidemiology of leishmaniasis in some regions of the State of Pernambuco, the objective of this study was to evaluate the occurrence of infection by Leishmania spp. in wild, synanthropic and domestic animals. For this, the parasitological diagnosis was carried out through exfoliative cytology of the skin of cutaneous lesions, in addition to PCR of the L. donovani and L. braziliensis complex of blood and spleen, liver and skin biopsy of rodents and skunks captured in an endemic area for leishmaniasis in the state of Pernambuco. In the locations where synanthropic animals positive for Leishmania were captured, blood, skin, bone marrow and lymph nodes were collected from the canine population. As a result, amastigote forms and DNA from the L. donovani complex were detected in 8.3% (2/24) of synanthropic animals (D. albiventris and O. nigripes). In the canine population, 29.4% (15/51) of dogs reactive for Visceral Leishmaniasis, and 6.6% were parasitologically and molecularly positive for the L. donovani complex. Thus, it is concluded that skunks, rodents and dogs participate in the transmission cycle of the L. donovani complex.